The Importance of Local Capital Markets for Financing Development - Narayanaswamy, Meera; Blitzer, Charles; Carvajal, Ana (International Finance Corporation, Washington, DC, 2018)
Rudimentary markets for capital - for raising money and investing - exist in even the remotest places around the world. However, prudent macroeconomic management, regulation, investor protection, and innovation are necessary to transition these nascent markets, which are often speculative ventures prone to fraud, into modern, efficient, and well-functioning markets capable of serving the needs of investors and entrepreneurs, borrowers, and lenders alike. Developing local capital markets and making greater use of them to fund private investment and strategic economic needs tends to happens in stages. The experiences of countries across the globe shows that capital markets development is a gradual process requiring strong leadership from government authorities as well as a significant commitment of time and resources. If done correctly, the payoffs can be substantial and long-term. The strategic imperative, however, is to develop strategies that fit the particular country circumstances.